2000
DOI: 10.1159/000053996
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Encoding Enzymatically Active HIV-1 Reverse Transcriptase, but Not the Inactive Mutant, Confers Resistance to Experimental HIV-1 Challenge

Abstract: The present study was undertaken to examine the immunogenicity of a single plasmid DNA representing the reverse transcriptase (RT) of HIV-1. Plasmids containing the enzymatically active RT as well as a mutated nonenzymatically active RT with nucleotide (nt)-binding motifs of YMDD and YMLL, respectively, were used to immunize mice. Both constructs induced similar good antibody and T cell responses, with a tendency towards antibody directed to peptides representing the active and mutated sites. Immunized mice we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 15 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…In contrast to other small animal models for HIV, we have a non-pathogenic in vivo model [Andäng et al, 1999;Isaguliants et al, 2000;Spetz et al, 2002]. Even though the analysis of protective immunity or the capacity to measure clearance of HIV-infected cells in vivo is restricted to a 2-week period after the challenge, we believe that this model could function as an inexpensive small animal model to test experimental HIV vaccines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to other small animal models for HIV, we have a non-pathogenic in vivo model [Andäng et al, 1999;Isaguliants et al, 2000;Spetz et al, 2002]. Even though the analysis of protective immunity or the capacity to measure clearance of HIV-infected cells in vivo is restricted to a 2-week period after the challenge, we believe that this model could function as an inexpensive small animal model to test experimental HIV vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Using such pseudotyped virus, HIV-1 genes could be delivered to murine spleen cells, as we have shown in vitro [Andäng et al, 1999]. It proved possible to infect both murine macrophage cell lines and T-cell lines with HIV-1 even though the virus replication is considerably lower than in human T cells [Dickie et al, 1996;Andäng et al, 1999;Isaguliants et al, 2000]. The aim of the present study was to transfer infected cells to establish an in vivo model and to define the HIV-1-specific immune responses elicited by the infection.…”
Section: Introductionmentioning
confidence: 95%
“…Using such a pseudovirus, we have previously shown that it is possible to deliver HIV-1 genes into murine splenocytes (26). We have also demonstrated that HIV-1/MuLV-infected splenocytes can provide a continuous release of infectious HIV-1 in vivo and in vitro 4 (27). HIV-1 RNA and isolation of infectious HIV-1 could be demonstrated up to 14 days after inoculation with live HIV-1/MuLV-infected cells.…”
mentioning
confidence: 93%
“…The wildtype RT DNA induces anti-RT specific IgG titers [32]. The wild-type RT plasmid (pRTwt) and the YMDD mutated RT plasmid (pRTmut) were compared head-to-head as immunogens, and induction of similar antibody titers was seen [10] (Fig. 2C).…”
Section: The Rt Dna Immunogenmentioning
confidence: 89%
“…One of the most potent of all HIV-1 antigens in eliciting CTL reactivity is the Gag (p24) antigen, and ongoing trials with the Gag antigen show promising induction of cellular immunity in primates and humans (reviewed in [9]). The HIV-1 reverse transcriptase (RT) has also been evaluated and experimental challenge experiments suggesting that it is a potent vaccine target [10]. The generation of CTL against epitopes that are conserved among different strains of HIV is the rationale for focusing upon CTL and these antigens.…”
Section: The Evolution Of Hiv Vaccine Developmentmentioning
confidence: 99%